Internal Short Circuit Analysis of Cylindrical Lithium-Ion Cells Due to Structural Failure. Issue 3 (16th March 2021) - Sheikh, Muhammad; Elmarakbi, Mohab; Rehman, Sheikh; Elmarakbi, Ahmed
Abstract : Battery failures are obvious after being subject to abuse conditions however predicting these failures in advance is crucial when using test and validation techniques to understand battery potential. Lithium-ion battery cells are widely used due to their high energy and power densities. When abusive conditions like the three-point bend loading are applied to lithium-ion batteries, what occurs to the mechanical behaviours and components is still mostly unknown. To further this understanding, this paper investigates the mechanical behaviour of the separator in the LiCoO2/Graphite cylindrical 18650 cells. Internal short circuit (ISC) behaviour, strain rate dependency, and electrochemical status of the cells (i.e. SOC dependency) are studied to understand failure patterns. Furthermore, a simple and effective constitutive model for the separator layer is formed, facilitating further mechanical analysis and numerical simulation of lithium-ion battery study. The occurrence of ISC is investigated by jellyroll deformation where the casing is removed, and quasi-static load is applied. A numerical simulation model is developed to further investigate sequential structural failures and temperature changes. Simulation results showed good accuracy with experimental results and are useful to predict structural failure of cells. The number of failures including electrolyte leakage, change in shape, sudden voltage drop/temperature rise, and gas venting is observed.